2002
DOI: 10.1007/s00253-002-0951-6
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic degradation of 2,4,6-trichlorophenol by a microbial consortium - selection and characterization of microbial consortium

Abstract: A microbial consortium that efficiently degrades 2,4,6-TCP (2,4,6-trichlorophenol), as the sole source of carbon and energy under aerobic conditions was selected from municipal activated sludge. Six bacterial strains, designated S(1), S(2), S(3), S(4), S(5) and S(6), were isolated from the selected consortium and five were identified as Sphingomonas paucimobilis (S(2), S(3)), Burkholderia cepacia(S(4)), Chryseomonas luteola (S(5)) and Vibrio metschnikovii (S(6)). After prolonged cultivation followed by success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The results obtained by HPLC confirmed that after 48 h incubation both 246TCP and 246TBP were completely degraded in all microcosms. A similar result was informed by Kharoune et al (2002) in a bacterial consortioum able to degrade 246TCP. The authors indicated that the consortioum required a 15 day adaptation period to begin degradation, and after successive additions of chlorophenol, the degradation rate increased four times without requiring an adaptation period.…”
Section: Halophenol Degradation In the Water Samplessupporting
confidence: 79%
See 2 more Smart Citations
“…The results obtained by HPLC confirmed that after 48 h incubation both 246TCP and 246TBP were completely degraded in all microcosms. A similar result was informed by Kharoune et al (2002) in a bacterial consortioum able to degrade 246TCP. The authors indicated that the consortioum required a 15 day adaptation period to begin degradation, and after successive additions of chlorophenol, the degradation rate increased four times without requiring an adaptation period.…”
Section: Halophenol Degradation In the Water Samplessupporting
confidence: 79%
“…Due to their constant use, these compounds are common pollutants of soils and freshwater. Fulthorpe and Schofield (1999) reported that microorganisms recently developed the ability to degrade halogenated aromatic compounds as a response to their use as pesticides, even as sole carbon and energy source (Kharoune et al 2002;Sánchez et al 2004;Yamada et al 2008). Nevertheless, several studies have shown that bacteria isolated from environments not exposed to this type of pollutant are able to degrade organochlorinates (Kamagata et al 1997;Sánchez et al 2004).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of the four isomers of trichlorophenols investigated in this study (2,4,6-TCP, 2,4,5-TCP, 2,3,6-TCP, and 3,4,5-TCP), the 2,4,5- and 2,4,6-isomers are listed on the US EPA's priority pollutants list. The latter has been included in Directive 76/464/EEC (European Economic Community) as a dangerous substance discharged into the aquatic environment [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%